PESANTREN EDUCATION IN AN EFFORT TO CONTROL RADICALISM - SHOLIH MUADI (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this article is to describe and explain pesantren education in controlling radicalism. The article approach method is through literature review and theory approach. The results suggest that Islamic boarding schools apply the principles of tasamuh (tolerant), tawasuth wal i'tidal (simple), tawazun (full of consideration) and ukhuwah (brotherhood). So that pesantren education is very strategic in controlling radicalism and transforming a culture of peace. The pesantren education system has a distinctive style which is the branding of the pesantren. The system is, character education and character education. Character education shapes the character of students through a teaching material approach that emphasizes important material into character. Meanwhile, character education forms a character that is close to a strong character for their life. Pesantren as a forum for galvanizing Muslims need to transfer peace as a form of Islam as rahmatan lil 'alamin, both to fellow Muslims and the community so that there are no more cases of conflict driven by the pesantren. A complete understanding of Islam makes the pesantren community always spread human values ​​and peace.